Doença de Parkinson secundária a Covid-19: uma revisão sistemática - BRAGA, Gabriel Hans Reis (2023)
Objective: This study aimed to carry out a systematic review of Parkinson's Disease and its relationship with COVID -19. Methods: We used and adapted the criteria present in PRISMA (Preferred Reporting Items for Systematic Reviews and MetaAnalyses) and aimed to identify peerreviewed publications on the topic of Parkinson's disease related to COVID-19. Results: Parkinson's disease after COVID19 is present in some cases and seems to be related to mechanisms of hyperinflammation mediated by SarsCov2, especially in patients under 60 years of age. Conclusion: The occurrence of Parkinson's disease after an infection with the new coronavirus seems to be explained by the cytolytic effects of the virus, accumulation of intracellular proteins, epigenetic modifications and interactions in inflammatory pathways that cause neuronal death. COVID-19 is also associated with worsening of the symptoms in people with previously diagnosed Parkinson's Disease.